A Study on the Use of Nichrome Wire to Ease the Flow of Heavy Crude Oil in Pipelines - Wafaa Rashid Al-Mahrooqi; Girma T. Chala (Platform, a Journal of Engineering)
Production of waxy crude oil poses significant challenges due to high wax contents, which negatively affects the production rate. Several techniques have been adopted to ensure the flow of heavy crude oil during production. However, many of the methods appear costly and pose challenges during installation. Therefore, this study aims to investigate using nichrome wire for heavy crude oil production. An experimental setup was developed to power the nichrome wire placed inside the production casing. It was observed that the temperature increased with the decrease in the diameter of the nichrome wire. Heavy crude oil’s maximum temperature was 72.3°C for a diameter of 0.05 mm, while it was 63.2°C for light crude oil. Nichrome wire withstands a high temperature, reaching 1150°C, which would help reduce the viscosity of the crude oil.